Advancing diagnosis of feline Leishmania infantum infection through experimental insights - Akhtardanesh Baharak; Mostafavi Ali; Mostafavi Mahshid; Zamani-Ahmadmahmudi Mohamad; Sharifi Iraj; Abbaszadeh Hasiri Mohammad; Kheirandish Reza; Hajipour Pooneh; Barkhordarnasab Azimeh; Shokrollahi Nasim; Keyhani Alireza; Sina kakooei (Scientific Reports)
Abstract In this study, we aimed to identify the clinical findings and efficacy of different diagnostic methods in feline visceral leishmaniasis (FVL) experimental model. Healthy adult cats were divided into trial and control groups. The first and second trial groups received 108 and 109 promastigotes of leishmania infantum (L. infantum) in the stationary phase intravenously and sterile isotonic distilled water (DW) was inoculated for control cats by the same volume and route. The follow-up examination was done up to 24 weeks post-inoculation(PI). Daily clinical examination and monthly blood sampling were done for serological, molecular, hematological, and biochemical evaluations. Bone marrow (BM) aspiration was started from the second month and repeated every 2 months until the end of study. Finally the cats were euthanized and histopathological examination and organ culture were performed. The blood and bone-marrow samples of all inoculated cats were positive at nested polymerase chain reaction (N-PCR) from the second and 8 weeks PI respectively and remained positive during the study. L. infantum amastigotes were detected in BM direct smear after 12 weeks and BM culture was positive at this time. N-PCR of Liver and lymph nodes, were positive in three cats in each experimental groups. In histopathological examination, amastigotes were not observed in organs but sinus histiocytosis in the spleen and lymphoid hyperplasia were the major histopathological changes. All cats remained seronegative in enzyme-linked immunosorbent assay (ELISA) until the end of the study. All infected cats had a reasonable healthand no significant alteration in laboratory findings was noted. Long-lasting parasitemia and the presence of L. infantum in bone marrow, revealed that cats could be considered as secondary reservoirs for L. infantum. N-PCR is the best screening diagnostic method because the humoral immune response is not well activated in the feline model and antibody titers were not detected in the initial phase of L. infantum infection. Further studies are crucial to elucidate the immune system function and pathogenesis of L. infantum in cats.